Health Education Interventions to Improve Cervical Cancer Screening Behavior: A Scoping Review - Firda Dwi Anugrah; Ditya Yankusuma Setiani; Durrotul Qomariyah; Siti Romlah; Eka Suryaning Tyas (Universitas STRADA Indonesia, 2026)
Background: Cervical cancer is one of the most common cancers and the fourth leading cause of death among women worldwide. Several factors influencing cervical cancer screening behavior include knowledge and attitudes toward screening, relationships between patients and health care providers, and fear of test results. Purpose: This study aimed to identify the provision of health interventions in improving cervical cancer screening behavior. Methods: The method used in this study was a scoping review of 11 selected articles. The findings showed that six articles reported health education using audio visual media, which significantly increased cervical cancer screening behavior. Three articles examined the use of social media, although one study found that social media did not significantly improve screening behavior. In addition, three articles used conventional educational methods and demonstrated significant improvements in cervical cancer screening behavior. Results: Overall, the review indicates that increasing knowledge is a key factor in encouraging women to participate in cervical cancer screening. Conclusion: Adequate understanding can improve awareness, willingness, and ability to undergo screening. Future studies are recommended to compare the effectiveness of various health education media to support their implementation in health services. Nurses, as educators and counselors, have an important role in providing sufficient information and influencing the community regarding the importance of cervical cancer screening.